Nelson Mandela - Akinyemi, Rowena (Oxford : Oxford University Press, 2008)
In 1918 in the peaceful province of Transkei, South Africa, the Mandela family gave their new baby son the name Rolihlahla - "troublemaker". But the young boy's early years were happy ones, and he grew up to be a good student and an enthusiastic sportsman. Who could imagine then what was waiting for Nelson Mandela - the tireless struggle for human rights, the long years in prison, the happiness and sadness of family life, and one day the title of President of South Africa? This is the story of an extraordinary man, recognized today as one of the world's great leaders, whose long walk to freedom brought new hope to a troubled nation .
Includes index.
Contains activities
Keywords: Mandela, Nelson, -- 1918-2013 -- Biographies; English language -- Textbooks for foreign speakers; Reading comprehension -- Problems, exercises, etc